(untitled) (Journal of Management and Social Sciences, 2017)
Abstract The study examined the relationship between foreign direct investment and financial development in Nigeria for the period 1980 to 2015. Using the vector error correction model (VECM) technique, the study observed a negative relationship existed between financial market development and foreign direct investment in the long run while in the short run, a positive relationship existed between financial market development and foreign direct investment in Nigeria over the estimated period of 1980-2015. Therefore, the study recommended further development of the Nigerian financial market by the monetary authority given its positive influence on the inflows of foreign direct investment in the short run. There is also the need for more financial reform of the Nigerian financial system in order to bring more foreign direct investment into the country both in the long and short runs. Â Keywords Â Financial development, Foreign Direct Investment, VECM, Nigeria